Optimasi Dosis Pupuk Nitrogen dan Fosfor pada Tanaman Kelapa Sawit (Elaeis guineensis Jacq.) Belum Menghasilkan Umur Satu Tahun - Shintarika, Feni; ,, Sudradjat; ,, Supijatno (Indonesia Society of Agronomy (PERAGI) and Department of Agronomy and Horticulture, Faculty of Agriculture, IPB University, Bogor, Indonesia, 2015)
ABSTRACTThe accuracy of fertilizer dosage for one-year-old oil palm plants is very important. The objective of the research was to determine the optimum rates of Nitrogen and Phosphorus fertilizers for young oil palm. The experiment was conducted at IPB-Cargill Teaching Farm of Oil Palm at Jonggol, from March 2013-March 2014. This study consisted of two separate experiments namely (1) Optimizing Nitrogen and (2) Optimizing Phosphorus. Both experiments used randomized block design with one factor and three replications. The treatments were five rates of nitrogen or phosphorus (0, 135, 270, 405, 540 g N per plant; 0, 135, 270, 405, 540 g P2O5 per plant). The results showed that nitrogen fertilizer rates increased height linearly at 10 month after treatment (MAT) and quadratically at 12 MAT. Stem girth, frond production and leaf area of 9th frond increased quadratically with N rates (9, 10, 12 MAT). Nitrogen fertilizer quadratically increased leaf chlorophyll content (12 MAT), but did not significantly affected leaf-N content. Phosphorus fertilizer increased palm height linearly (9, 10 MAT) and quadratically (12 MAT). Phosphorus linearly increased stem girth (12 MAT) and quadratically (9, 10 MAT). Frond production was quadratically increased with phosphorus rates (9, 10, 12 MAT). Phosphorus linearly increased leaf area of 9th frond (9 MAT) and quadratically (12 MAT). The optimum rates of nitrogen and phosphorus fertilizers for one year old plant was 382 g N and 331 g P2O5 per plant, respectively.Keywords: inorganic, nutrient, optimum rates, single fertilizer